IPTEKS STANDAR AKUNTANSI KEUANGAN NO. 28 PADA PT ASURANSI ADIRA DINAMIKA CABANG MANADO - Iroth, Natasia; Mamangkey, Greyshella Sesdi; Mawikere, Lidia M (Universitas Sam Ratulangi, 2018)
Insurance is an institute who have important role in the economy. Companies are asked to manage and compile their financial statements, because that is an important thing that will greatly affect the company's productivity. For this reason, in every company have to apply be valid accounting standards to make information that is can understood by wearer of financial statements. In the presentation of financial statements, the income statement is a very important component, especially for calculation’s company expenses and income. Then it is necessary to recognize and record properly and in accordance with be valid standards. The aim of this research is to analyze the conformity of recognition of company income and expenses and PSAK No. 28 concerning Accounting for loss insurance contracts. The method used is the analysis of profit and loss statements with components in which the income and expense of PT Asuransi Adira Dinamika branch of Manado with PSAK No. 28. From the results of this study it was concluded that PT Asuransi Adira Dinamika Manado branch has recognized revenue and expenses appropriately according to standards, namely revenues recognized at the time of issuance of policies (contracts) and claims expenses recognized as expenses when issuing work orders (SPK) from headquarters. The company applies the accrual basis method in recognition of revenues and expenses, where transactions are recorded and reported at the time of the event and not when cash or cash equivalents are received (paid). Each company transaction is inputted systemically from the branch office to the head office in accordance with the detailed classification.Keywords : Revenue, Expense, Insurance, PSAK. N0 28